### Exponents and Powers - Worksheets

CBSE Worksheet-1

CLASS –VII Mathematics (Exponents and Powers)

Choose correct option in questions 1 to 4.

1. Find the value of $\left(-9{\right)}^{3}×\left(-4{\right)}^{2}.$
a) -11664
b) 36
c) 5
d) 25
2. Simplify: ${7}^{x}×{7}^{2}$
a) 7x+3
b) 7x+2
c) 72x
d) 7x-2
3. Which is greatest among the following?
a) 82
b) 43
c) 28
d) 32
4. Find the value of $\left({6}^{0}-{2}^{0}\right)×\left({6}^{0}+{2}^{0}\right).$
a) 2
b) 1
c)3
d) 0
5. In (-9)4, the base is _______ and the exponent is 4.
6. (-1)4 is equal to ____.
7. (ax)y = _____
8. What should be added to 2y- 4yz - 2z2 to get y- 2yz - z2.
9. Express the following numbers in the standard form.
a) 5,223,000,000
b) 256,000,000
10. Simplify and write the answer in exponentialform.
a) 37÷ 34
b) 58÷ 54
11. Find m when ${\left(\frac{2}{9}\right)}^{3}×{\left(\frac{2}{9}\right)}^{-6}={\left(\frac{2}{9}\right)}^{2m-1}$

CBSE Worksheet-1
CLASS –VII Mathematics (Exponents and Powers)

1. b ; { 7x x 72 = 7x+2 ( when bases are same and there is a sign of multiplication in between then the exponents get added) }
2. c ; { 82 = 64 , 4= 64, 28 = 256, 32 = 9 }
3. a; { (60 - 20) × (60 + 20) = ( 1 - 1 ) x ( 1 + 1) = (0) x ( 2) = 0 ( any base number with exponent 0 is equal to 1) }
4. -9
5. 1
6. axy ; { in this case exponents will get multiplied }
7. (y- 2yz - z2 ) - ( 2y- 4yz - 2z2)
=  y- 2yz - z- 2y2 +4yz +2z2
= - y2 + 2yz + z2
8. a. 5.223 x 109
b) 2.56 x 108
9. a) 3; { 3 7-4 when the bases are same and there is a sign of division in between then the exonents get subtracted }
b) 54 ;{ 58-4 when the bases are same and there is a sign of division in between then the exonents get subtracted }
10. ${\left(\frac{2}{9}\right)}^{3\phantom{\rule{thickmathspace}{0ex}}+\phantom{\rule{thickmathspace}{0ex}}\left(-6\right)}\phantom{\rule{thickmathspace}{0ex}}=\phantom{\rule{thickmathspace}{0ex}}{\left(\frac{2}{9}\right)}^{2m-1}$
$={\left(\frac{2}{9}\right)}^{-3\phantom{\rule{thickmathspace}{0ex}}}=\phantom{\rule{thickmathspace}{0ex}}{\left(\frac{2}{9}\right)}^{2m-1}$
$⇒$ 2m - 1 = -3
2m = -3 + 1
2m = -2
$m=\frac{-2}{2}$
m = -1